Representing the Experience: the Act of Remembering on Patricio Larrambebere ́s Marcas Serie of Paintings (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
During the mid-90s, in the city of Buenos Aires, a set of artistic productions converged in the construction of representational systems in order to question the identity models and experience that the neoliberal culture had established. This article aimsto study said repositioning by focusing on the Marcas series produced by Patricio Larrambebere. This series connects and contrasts graphics that refer to the national industry and different corporalities relating to the industry. Through the different modalities that the pictorial work acquires, the action of remembrance that the work promotes coincides with the indication of a present at risk.
Keywords: Argentine Contemporary Art; Neoliberal Culture; History Painting; Arts and Memory.